Social entrepreneurship as the basis of social responsibility of enterprises in the context of digital transformations based on the mechanism of cross-sectoral interaction - Korytko, T.; Piletska, S. (Економічний вісник Донбасу, 2024)
The preservation and multiplication of the welfare of society is a task that in modern times should be paired with measures that contribute to the reduction of social tensions and differentiation in society. In the context of the digitalization of the economy, society requires from business a conscious approach to solving social problems, a developed sense of civic responsibility in relation to other social groups. Entrepreneurship is one of the most important social institutions of our time. It is able to assist state structures in solving social problems by developing the infrastructure of the region, working with low-income groups of the population. In modern conditions in Ukraine, the spread of social entrepreneurship is fragmented and is at the initial stage of development. Undoubtedly, the universal digitalization of economic processes cannot but affect the social sphere of entrepreneurship, in this regard, the task of finding the most comfortable model of digital transformation is actualized. The innovative phenomenon of social business determines the choice of research methods in favor of tools for the transformation of classical business models in a digital economy, as well as methodological and organizational aspects of the functioning of subjects of social entrepreneurship. The methodology of general scientific knowledge will allow to form the author's approach to the theoretical and methodological justification of the mechanism of digital transformation of social business. The need to create a high-quality institutional base for the development of social entrepreneurship is substantiated and steps are outlined for the development of social enterprises to fulfill their social mission. The obtained results can be used to strengthen the relationship between the state, business and society, which will become a new driver of economic development in the context of digital transformation. Збереження та примноження добробуту суспільства – це завдання, яке в сучасних умовах необхідне сполучати з заходами, що сприяють зниженню соціальної напруженості та диференціації у суспільстві. В умовах цифровізації економіки суспільство вимагає від бізнесу усвідомленого підходу до вирішення соціальних проблем, розвиненого почуття громадянської відповідальності стосовно інших соціальних груп. Підприємництво – один із найважливіших соціальних інститутів сучасності. Воно здатне сприяти державним структурам у вирішенні соціальних проблем шляхом розвитку інфраструктури регіону, роботи із малозабезпеченими групами населення. В сучасних умовах в Україні поширення соціального підприємництва носить фрагментарний характер та перебуває на початковій стадії розвитку. Безумовно, загальна цифровізація економічних процесів не може не торкнутися соціальної сфери підприємництва, у зв'язку з чим актуалізується завдання пошуку найкомфортнішої моделі цифрової трансформації. Інноваційний феномен соціального бізнесу визначає вибір методів проведення дослідження на користь інструментів трансформації класичних бізнес-моделей у умовах цифрової економіки, а також методичних та організаційних аспектів функціонування суб'єктів соціального підприємництва Методологія загальнонаукового пізнання дозволять сформувати авторський підхід до теоретичного та методичного обґрунтування моделі цифрової трансформації соціального бізнесу. Обґрунтовано необхідність створення якісної інституційної бази для становлення соціального підприємництва та окреслено кроки для розвитку соціальних підприємств для виконання ними соціальної місії. Отримані результати можуть бути використані для зміцнення взаємин держави, бізнесу та суспільства, що стане новим драйвером економічного розвитку умовах цифрової трансформації.